Organising Visual Information Of Traditional Ornaments Adorned By Embhan’s Ring Ladies - Yakup, Mohd Rafee; Awangko Hamdan, Awang Arshad; Hishamuddin, Siri; Sylvester Wielding, Jussem; Sarah Naemah, Aman Leong; Doris, Maying (Human Resource Management Academic Research Society (HRMARS), 2018)
This article aims to discuss an alternative system to organize information in the context of visual ethnography study particularly on the documentation of diminishing traditional ornaments worn by the remaining Ring Ladies of Embhan Community, the only community in Sarawak who still practice this culture. The system was developed based on problems faced by the researcher when visual and data collected during the investigation has difficulty with storage due to the lack of a systematic compilation method. Thus, it is challenging for the researcher to identify or retrieve the information, especially relating to visual data on the cultural objects. Through visual ethnography method, visual information related to cultural objects of Bidayuh Embhan particularly with the Ring Ladies was collected and analyzed. Hence, an alternative system in organizing visual information relating to the cultural object called, Digital Ethnographic Organizer (e-Divo) was created using Adobe InDesign and published in a Flash format. It is hoped that this system can be developed further as an information seeking tool that can be used in the context of cultural objects and ethnography exhibition, especially in the galleries or museums.